God or the girl [videorecording (DVD)] (A&E Television Networks ; Distributed in the U.S. by New Video, 2006)
A serious exploration of some of the questions surrounding religious vocation in an aggressively secular culture, the series chronicles several emotional weeks in the lives of four young men as they struggle with the decision to enter the seminary and become Roman Catholic priests. All grapple with the sacrifices they would have to make should they enter the priesthood, including the vow of celibacy. And all of them do unusual things things, often at the suggestion of their spiritual mentors, that they hope will guide them toward the right path.